Role of wing morphing in thrust generation - Mehdi Ghommem; Muhammad R. Hajj; Philip S. Beran; Ishwar K. Puri (Theoretical and Applied Mechanics Letters, 2014)
In this paper, we investigate the role of morphing on flight dynamics of two birds by simulating the flow over rigid and morphing wings that have the characteristics of two different birds, namely the Giant Petrel and Dove Prion. The simulation of a flapping rigid wing shows that the root of the wing should be placed at a specific angle of attack in order to generate enough lift to balance the weight of the bird. However, in this case the generated thrust is either very small, or even negative, depending on the wing shape. Further, results show that morphing of the wing enables a significant increase in the thrust and propulsive efficiency. This indicates that the birds actually utilize some sort of active wing twisting and bending to produce enough thrust. This study should facilitate better guidance for the design of flapping air vehicles.